A Global Communication M.A. Double Degree Program: Conceptualizing and Working Through Diversity (Global Media Journal - German Edition, 2021)
At a time when diversity and de-westernization are current buzz words for injecting social justice into the future of communication studies, we must address how we conceptualize and confront these concepts in practice. Academic Cosmopolitanism has been proposed as one way forward, but it remains in the trenches of cosmopolitan theory’s difficulty of dealing with diversity in political systems. Simon Fraser University and the Communication University of China’s Global Communication MA Double Degree Program embodies many of the core values of academic cosmopolitanism. Grounded in a transcultural political economy framework however, it embraces some of the kinds of conflicts that cosmopolitanism sets up as barriers. Via autoethnographic accounts from the program’s first teaching assistant and an alumnae from its first cohort, we explore how the conflicts involved in conceptualizing and confronting diversity are experienced on the ground. We conclude by highlighting the ways in which transcultural political economy enriches discussions on diversity and inform efforts to de-colonize communication studies.
Keywords: Acaacademic cosmopolitanism; transcultural political economy; diversity; transformation; de-westernization